Citizens’ Communication Habits and Use of ICTs During Crises and Emergencies - Haataja, Matti; Hyvärinen, Jenni; Laajalahti, Anne (Human Technology, 2014)
In this article, citizens’ communication habits and use of information and communication technologies during crises and emergencies are discussed from the perspective of community resilience. The topic is approached qualitatively by exploring citizens’ perceptions, and the data were gathered by means of focus groups in storm-prone and flood-prone areas in Finland. The results indicate that citizens consider emergency communication to be mostly unidirectional: from authorities to the public. However, because crises are often complex and fast developing, cooperation among response organizations and citizen groups is needed to coproduce safety and in adapting to changing situations. Organizations wanting citizens to participate proactively in emergency management should raise citizens’ awareness of the means and possibilities to contribute, because these informants’ expectation that authorities would welcome their input was low. Based on the results, public participation could be supported further by credible actors, such as local volunteer organizations.